2007
DOI: 10.1016/j.ijfatigue.2007.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of dissipated energy and other fatigue criteria☆

Abstract: Amongst a large number of fatigue criteria proposed for the prediction of crack initiation in thermomechanical fatigue, various approaches have been found to be particularly useful for certain categories of material over specific domains of temperature and cyclic strain. However, no particular approach appears to give invariably better predictions than others, so that the choice of the lifing model must be based on validation for the relevant circumstances.In this paper the focus is placed on the Energy Dissip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(92 citation statements)
references
References 16 publications
0
92
0
Order By: Relevance
“…Another study established the usefulness of p for predicting the experimentally-observed FCI sites for explicit ferritic steel microstructures under four-point bending fatigue [24]. The second FIP used is a crystallographic work parameter [26], W, which sums strain energy dissipation over all slip systems:…”
Section: Hcf Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study established the usefulness of p for predicting the experimentally-observed FCI sites for explicit ferritic steel microstructures under four-point bending fatigue [24]. The second FIP used is a crystallographic work parameter [26], W, which sums strain energy dissipation over all slip systems:…”
Section: Hcf Predictionsmentioning
confidence: 99%
“…A crystallographic work parameter [26], W, has also been successfully used to predict the experimentally-observed FCI site for an austenitic steel [27].…”
Section: Introductionmentioning
confidence: 99%
“…Then the slip ratio ( Fig. 2) can be defined as the ratio of the slip and displacement amplitudes [1][2][3][4][5]. However, from an experimental standpoint, by neglecting the end effects at the extremities of the hysteresis loop, the slip ratio can be also calculated as the ratio between the dynamic and static friction forces ( Fig.…”
Section: Slip Ratio and Slip Indexmentioning
confidence: 99%
“…Depending on the loading conditions, material properties and environment, fretting can cause fretting wear, which combines all four basic mechanisms (oxidative, adhesive, surface fatigue and abrasive), or fretting fatigue, which combines surface and bulk fatigue [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Fretting wear and fatigue severely decrease the life of machine elements (e.g., rolling element bearings, screw and rivet assemblies, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…In the last decades, many analytical surrogate metrics for the small crack driving forces, which are commonly known as fatigue indicator parameters, have been postulated, 21,[32][33][34][35] albeit seldom of these theories have been directly compared to 3D experimental data. [36][37][38] Due to the nature of their construction, these fatigue metrics would benefit from a systematic analysis of the variables possibly influencing the small crack propagation process.…”
Section: Introductionmentioning
confidence: 99%